"Ireland and Croatia: West and East", 23.-25.09.2011., Ireland East and West, Filozofski fakultet, Sveučilište u Zagrebu (u su-organizaciji s Trinity College Dublin, uz potporu irskog veleposlanstva) - Gjurgjan, Ljiljana Ina (2011)
This paper adresses the question of cultural comparativism and its relevance for understanding the operations of cultural signification. The Yeats/Joyce and Nazor/Kamov dichotomies will be examined as paradigmatic of the creation of (anti-)colonial discourses. Particular attention will be given to the political implications of the 'hot' (YEats, Nazor) vs. 'cold' (Joyce, Kamov) rhetorics (Deane) and especially how they operate in terms of national/gender stereotypes through paternal/maternal metaphors. In the conclusion, it briefly exposes this discussion to the post-Modernist tendency to relativize not only the 'hot' and 'cold' discourses of Yeats/Joyce and Nazor/Kamov, but also to deconstruct any kind of cultural binarism, not least the binarism between the colonizer and the colonized.